2015
DOI: 10.1128/aac.04942-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Pharmacodynamic Effect of Antimalarial Drugs in Clinical Trials by Quantitative PCR

Abstract: cThe ongoing development of new antimalarial drugs and the increasing use of controlled human malaria infection (CHMI) studies to investigate their activity in early-stage clinical trials require the development of methods to analyze their pharmacodynamic effect. This is especially so for studies where quantitative PCR (qPCR) is becoming the preferred method for assessing parasite clearance as the study endpoint. We report the development and validation of an analytic approach for qPCR-determined parasite clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…In part 2, log 10 PRR 48 and parasite clearance half-life were estimated using the slope of the optimal fit for the log-linear relationship of the parasitaemia decay 21 . Individual log 10 PRR 48 and corresponding 95% CI were calculated using the slope and corresponding SE of the optimal regression model.…”
Section: Methodsmentioning
confidence: 99%
“…In part 2, log 10 PRR 48 and parasite clearance half-life were estimated using the slope of the optimal fit for the log-linear relationship of the parasitaemia decay 21 . Individual log 10 PRR 48 and corresponding 95% CI were calculated using the slope and corresponding SE of the optimal regression model.…”
Section: Methodsmentioning
confidence: 99%
“…Blood for PK assessment of 451840 was sampled pre-dose, at 0.5, 1, 2, 3, 4, 6,8,10,12,14,16,20,24,48,72,96 and 144 h after drug administration. The bioanalytical methods were the same as previously reported [6].…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…Further samples were taken on an individual basis until the last artemether/lumefantrine dosing day and at the final visit (day 28/end of study). Previous studies had indicated that following treatment with some licensed antimalarial drugs, such as sulfadoxine/pyrimethamine [14] and piperaquine [15], gametocytaemia becomes apparent after drug treatment. As an exploratory analysis, to test if 451840 blocks the appearance of gametocytaemia, we undertook PCR analysis for the mature gametocyte-specific transcript pfs25 as previously described [15].…”
Section: Parasitological Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated similar value ranges in terms of clearance attributable to host-reactions to infection γ max (0.055-0.44) ( Supplementary Table S7) and drug action E max (0.065-0.33) ( Supplementary Table S9) across all drugs and drug action models. Commonly used measures of drug efficacy such as parasite clearance half-life 39 , summarize all parasite clearance in a single index number 40,41 when in fact parasite clearance is the net effect of multiple parasite clearance mechanisms 23 . Therefore, the inclusion of delayed removal of parasites affected by the drug into mechanistic parasite growth Figure 6.…”
Section: Discussionmentioning
confidence: 99%